2002
DOI: 10.1093/intqhc/14.suppl_1.57
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of supervisor-provider interactions in health care facilities in Zimbabwe

Abstract: The study concludes with recommendations to the Ministry of Health and Child Welfare on how the quality of supervision in Zimbabwe could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 1 publication
10
30
0
1
Order By: Relevance
“…The second aspect helped facilitators with continuous visualisation and problem solving beyond the geographical and temporal constraints of on-site visits, which are also common beyond the setting of this study [28]. The findings of this research indicate that through the use of MIM, supervisors and facilitators could trace developments in their groups more continuously and develop a more persistent problem-based support.…”
Section: Discussionmentioning
confidence: 92%
“…The second aspect helped facilitators with continuous visualisation and problem solving beyond the geographical and temporal constraints of on-site visits, which are also common beyond the setting of this study [28]. The findings of this research indicate that through the use of MIM, supervisors and facilitators could trace developments in their groups more continuously and develop a more persistent problem-based support.…”
Section: Discussionmentioning
confidence: 92%
“…In developing countries, the need for supervision was highlighted during the primary health care movement where remote workers were perceived as needing supervision to link them to the health system and to supplement their training. By the start of the decade, it was recognized that traditional supervision, emphasizing inspection and control of health workers, was not working and there was a move toward supportive or facilitative supervision focusing on providers’ needs and collaborative problem solving (15, 16). This move was influenced by the emergence of models of clinical supervision from high-income countries (17–25), which take varied theoretical and practical stances to supervision but have been criticized for failing to demonstrate how they can be practically applied (25, 26).…”
mentioning
confidence: 99%
“…Despite the recognized role that supportive supervision can play in performance and motivation, numerous studies from a range of countries and programs have found that supervision often has low coverage; low administrative focus; is irregular, unsupportive, and demotivating; and lacks adequate training for supervisors and problem solving or feedback mechanisms for providers (11, 16, 2732). For example, in a time-use study in Ghana, only 15% of workers reported feeling supported by their supervisor (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was difficult to find appropriate items to evaluate the key concept of joint problem solving. At an advanced stage (step 16), a publication [31] provided an idea for how to add ‘solving problems jointly’ as a latent variable (a variable that may not be directly observed but may be indirectly measured through a set of observable items) in section A, using phrases such as ‘engaged me in’ and ‘involved me in’.…”
Section: Methodsmentioning
confidence: 99%